Do Democracy and Investment Promote Regional Economic Performance? Evidance from Panel Data Analysis - Isma, Andika; Fitrianti, Retno; Alisyahbana, Andi Naila Quin Azisah; Diarra, Salim (Quantitative Economics and Management Studies, 2025)
This study investigates whether democracy and investment promote regional economic performance in Indonesia. It employs panel data for 34 provinces over the period 2021–2023, modelling real GRDP per capita as a function of provincial democracy, investment, central government transfers per capita, and population. The empirical analysis is conducted using EViews 13, comparing pooled OLS, random effects, and fixed effects specifications; Chow, Breusch–Pagan LM, and Hausman tests consistently indicate that the fixed effects model is the most appropriate. The estimation results show that provincial democracy, as measured by the Indonesian Democracy Index, does not exert a statistically significant direct effect on regional economic performance within the short observation window. By contrast, investment displays a positive and robust association with real GRDP per capita across specifications, confirming its role as the main proximate driver of regional growth. Central government transfers per capita and population do not exhibit a stable growth-enhancing effect and, in some cases, are weakly or negatively associated with regional output. The findings of this study indicate that, in the short run, investment is the key channel through which regional economies respond to institutional and fiscal environments, while democracy operates more as a deep institutional background whose economic impokact is not immediately visible in annual growth outcomes.